2021
DOI: 10.3938/npsm.71.1067
|View full text |Cite
|
Sign up to set email alerts
|

Learning the Resistance Coefficients of Pendulum Motion Using Balls of Various Sizes

Abstract: In order to obtain the damping and resistance coefficients of a pendulum, we constructed an optical system containing a photogate for measuring the speed of the pendulum at the lowest point of motion. The photogate consisted of a photoresistor, a laser, a mechanical body, and a pendulum ball. A 3D printer was used to produce the mechanical body and pendulum balls of various sizes. Furthermore, we used Arduino to automate measurement of the speed at the lowest point of motion and increase the precision. We foun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…Our study has re-investigated the effects of cross-section of the string on pendulum bobs of different mass, size and material. The values of the air resistance coefficients are found to be of the same order of magnitude as reported by others [5].…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…Our study has re-investigated the effects of cross-section of the string on pendulum bobs of different mass, size and material. The values of the air resistance coefficients are found to be of the same order of magnitude as reported by others [5].…”
Section: Resultssupporting
confidence: 86%
“…In [5] it has been reported that damping, contrary to expectations, is significantly more with pendulum bob of lighter mass. Our findings reveal that factors like mass, shape, size and thickness are all important but effects of size/shape and thickness are more significant than mass of the pendulum in affecting the coefficients of damping.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations